Western Apache Heritage People of the Mountain Corridor - Perry, Richard J. (University of Texas Press, 2021)
Mention "Apaches," and many Anglo-Americans picture the "marauding savages" of western movies or impoverished reservations beset by a host of social problems. But, like most stereotypes, these images distort the complex history and rich cultural heritage of the Apachean peoples, who include the Navajo, as well as the Western, Chiricahua, Mescalero, Jicarilla, Lipan, and Kiowa Apaches. In this pioneering study, Richard Perry synthesizes the findings of anthropology, ethnology, linguistics, archaeology, and ethnohistory to reconstruct the Apachean past and offer a fuller understanding of the forces that have shaped modern Apache culture. While scholars generally agree that the Apacheans are part of a larger group of Athapaskan-speaking peoples who originated in the western Subarctic, there are few archaeological remains to prove when, where, and why those northern cold dwellers migrated to the hot deserts of the American Southwest. Using an innovative method of ethnographic reconstruction, however, Perry hypothesizes that these nomadic hunters were highly adaptable and used to exploiting the resources of a wide range of mountainous habitats. When changes in their surroundings forced the ancient Apacheans to expand their food quest, it was natural for them to migrate down the "mountain corridor" formed by the Rocky Mountain chain. This reconstruction of Apachean history and culture sheds much light on the origins, dispersions, and relationships of Apache groups. Perry is the first researcher to attempt such an extensive reconstruction, and his study is the first to deal with the full range of Athapaskan-speaking peoples. His method will be instructive to students of other cultures who face a similar lack of historical and archaeological data